Clinical Implications of Peripheral CD3+CD69+ T-Cell And CD8+CD28+ T-Cell Proportions in Patients Prior to Radical Prostatectomy - Zhang, Yu; Zhang, Ziye; Zhang, Lina; Zhao, Sheng; Zhao, Jing; Ye, Qing; Gao, Yingli; Jiang, Chenyi; Cui, Di; Xia, Shujie; Han, Bangmin; Jing, Yifeng (Urology Journal, 2020)
Purpose: To investigate the clinical implications of CD3+CD69+ T-cells and CD8+CD28+ T-cells in the peripheral blood of patients prior to radical prostatectomy. Materials and Methods: A total of 91 prostate cancer (PCa) patients and 50 benign prostatic hyperplasia (BPH) patients were enrolled from January 2016 to December 2017. The proportions of CD3+CD69+ T-cells and CD8+CD28+ T-cells in the peripheral blood of PCa and BPH patients were detected by flow cytometry, and the association of these T-cell populations with pathological Grade Group and pathological TNM classification was evaluated. Data analysis was performed with SAS version 9.4 software. Results: The proportions of CD3+CD69+ and CD8+CD28+ T-cells in peripheral blood were higher in PCa patients than those in BPH patients. Multivariate analysis identified a higher CD3+CD69+ T-cell proportion as a risk factor for PCa (odds ratio (OR) = 4.783, P = 0.0013), but the diagnostic efficacy of the CD3+CD69+ T-cell proportion (area under the curve (AUC)=0.6833, P = 0.0003) for PCa was still inferior to that of the tPSA level (AUC=0.7531, P < 0.0001). The AUCs for CD3+CD69+ T-cell and CD8+CD28+ T-cell proportions for PCa were 0.6959 (P = 0.0372) and 0.6935 (P = 0.0395), respectively, among men with tPSA levels of 4.0-10.0 ng/mL. A lower CD3+CD69+ T-cell proportion was associated with higher pathological Grade Group (P=0.0074). Conclusion: The proportions of CD3+CD69+ T-cells and CD8+CD28+ T-cells in peripheral blood are potential diagnostic indicators for PCa. The preoperative proportion of CD3+CD69+ T-cells in peripheral blood may have prognostic value in terms of the pathological Grade Group in PCa.